The Economics of legal minimum wages - Rottenberg, Simon; American Enterprise Institute for Public Policy Research (Washington, D.C : American Enterprise Institute for Public Policy Research, 1981)
The book consists of twenty-one papers on various of the impact of Fair Labor Standard Acts (FLSA), comments on these papers by discussants, and an overview by the editor. In his introduction Rottenberg forcefully states the neoclassical case against minimum wage. In so doing, he anticipates many of the findings of the other papers. The articles fall into the following categories: effects on employment and human-capital formation among teenagers, effects on the industrial distribution of low-skilled labor, effects of differential rates for identifiable groups, macro- economic effects, effects of minimum wages outside the United States, determinants of voting outcomes regarding minimum wages, and effects on income distribution. There is also one article, by Ehrenberg and Schumann, on the overtime provision of the FLSA. Some articles do not fit neatly into one of these categories, but most concentrate on one of the issues listed.
Papers presented at a conference held at the American Enterprise Institute, Washington, D.C., Nov. 1 and 2, 1979.
Includes bibliographies.
rpm 13/04/2018
Loans
Keywords: Minimum wage; Labor supply; Human capital